CONSTRUCTION OF CULTURAL IDENTITY OF VAQUEIRO IN ‘O SERTANEJO’ [THE BACKLANDS] OF JOSÉ DE ALENCAR - Morais, Lucas Andrade de (Revista de Estudos Acadêmicos de Letras, 2021)
The representation of sertanejo man in literature is presented through traditions, values and beliefs constructed in that space, in this process we have vaqueiro as a genuine "sertanejo", because it allows interiorization of northeast, appearing the sertão. Therefore, this article aims to identify how cultural identity of vaqueiro is constructed in regionalist project of Alencariano. In the discussion it used as theoretical contributions about socio-historical context of vaqueiro and the vaquejada in Cascudo (2008) and Magalhães (1970), identity culture in Hall (2006), culture and popular culture in Ayala & Ayala (1987), Santos (1992), Bosi (1992) and Bauman (2001) and sertanist literature in Sodré (1964) and Bosi (1994). The corpus of research is literary work ’O sertanejo’ [The Backlands] (1875) by José de Alencar. The results showed construction of cultural identity of vaqueiro in Alencarian literature has physical, socio-affective and symbolic elements are marks of identity of vaqueiro and can be resignified, adapting to new social relations and cultural contexts.